Efektivitas Pendidikan Kesehatan Berbasis Virtual Reality terhadap Tingkat Pengetahuan Ibu Nifas dalam Perawatan Luka Perineum - Astin Nur Hanifah; Yarnita Yarnita; Fitri Andriani; Surtikanti Surtikanti; Adisty Dwi Treasa (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Background: Perineal wounds are a common health problem experienced by postpartum mothers after childbirth. Postpartum mothers' knowledge of perineal wound care significantly impacts the healing process, infection prevention, and postpartum comfort. Innovation in health education using Virtual Reality (VR) media is believed to enhance the learning experience, making it more interactive and accessible. Objective: To determine the effectiveness of VR-based health education in improving postpartum mothers' knowledge of perineal wound care. Methods: This study used a quasi-experimental design with a pretest-posttest control group approach. The sample consisted of 60 postpartum mothers divided into an intervention group (VR-based health education) and a control group (conventional health education). The research instrument was a validated perineal wound care knowledge questionnaire. Data were analyzed using paired t-tests and independent t-tests. Results: The results showed a significant increase in postpartum mothers' knowledge after receiving VR-based health education (p < 0.001). The average increase in knowledge scores in the intervention group was higher than in the control group. Conclusion: Virtual reality-based health education effectively improves postpartum mothers' knowledge of perineal wound care. VR media can be an innovative alternative in providing postpartum health education.